Academic outcomes and accommodations following adolescent sport-related concussion: a pilot study. (23rd October 2017) - Russell, Kelly; Selci, Erin; Chu, Stephanie; Rozbacher, Adrian; Ellis, Michael
Aim: The purpose of this study was to examine academic achievement, absenteeism and school accommodations following adolescent sport-related concussion (SRC).Methods: A case-series was conducted among grade 8–12 students who suffered an SRC. The primary outcomes were change in pre- and post-concussion overall, core report card grade point average (GPA) and absenteeism due to concussion. The most helpful school accommodations were tabulated.Results: Pre- and post-concussion GPA was obtained from 33 students – 16 (48%) developed persistent post-concussion symptoms (symptoms lasting >4 weeks). There was no significant difference in pre- and post-concussion grades among students with a SRC for overall (p = 0.75) or core (p = 0.56) GPA. The median number of missed school days was 4 (interquartile range [IQR]: 2–8). Allowing for physical and cognitive rest was identified as the most helpful accommodation (30%).Conclusion: Larger studies should investigate the role that school accommodations and development of persistent post-concussion symptoms have on academic outcomes.